Vaginoplasty tips and tricks - Li,Joy S. (2021)
ABSTRACT Vaginoplasty is a commonly performed surgery for the transfeminine patient. In this review, we discuss how to achieve satisfactory surgical outcomes, and highlight solutions to common complications involved with the surgery, including: wound separation, vaginal stenosis, hematoma, and rectovaginal fistula. Pre-operative evaluation and standard technique are outlined. Goal outcomes regarding aesthetics, creation of a neocavity, urethral management, labial appearance, vaginal packing and clitoral sizing are all described. Peritoneal vaginoplasty technique and visceral interposition technique are detailed as alternatives to the penile inversion technique in case they are needed to be used. Post-operative patient satisfaction, patient care plans, and solutions to common complications are reviewed.